2020
DOI: 10.2147/rru.s237824
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison Between Processus Vaginalis Sac Tightening Technique and the Conventional Technique in Orchiopexy Surgery Over 10 Years</p>

Abstract: Background: Undescended testis (UDT) is a common congenital urogenital anomaly that is treated by orchiopexy. We aimed to introduce patent processus vaginalis (PPV) sac tightening (PVST) technique and compare it to the conventional technique. Methods: We retrospectively studied all the operated UDT patients during 10 years. In the conventional technique, it was necessary to ligate PPV sac after being peeled off from the spermatic cord. PVST was dissected longitudinally from the two sides of where the PPV sac w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In this study, the recurrence rate was found to be lower in patients whose PPV was not closed. Some studies suggested should not close the PPV after dissection but other studies recommend not close the PPV may lead a inguinal hernia [12]. In this study inguinal hernia was not observed in any of patients.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In this study, the recurrence rate was found to be lower in patients whose PPV was not closed. Some studies suggested should not close the PPV after dissection but other studies recommend not close the PPV may lead a inguinal hernia [12]. In this study inguinal hernia was not observed in any of patients.…”
Section: Discussionmentioning
confidence: 51%
“…Dissection of PPV may lead a damage to spermatic cord and testicular vessels [12]. It's more risky in younger ages [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An orchiopexy is the surgical fixation of testicles in the scrotum (16). It can be performed through open surgery techniques or laparoscopy (17). The incidence of undescended testis (UDT) in humans is 1% in male infants, and it is considered as one of the most common congenital abnormalities in males (18).…”
Section: Discussionmentioning
confidence: 99%
“…High ligation procedures and contralateral PPV diagnostics were carried out in accordance with standard surgery procedures applicable at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. The surgical procedure includes when the hernia sac is opened, the probe is attached and tied so that compressed abdominal air does not come out, and a laparoscopy camera is inserted with a 30-degree lens unruly peeking at the PPV counterpart (17) .…”
Section: Methodsmentioning
confidence: 99%